Proteomic analysis of micro-scale bioreactors as scale-down model for a mAb producing CHO industrial fed-batch platform - Bertrand, Vania; Vogg, Sebastian; Villiger, Thomas K; Stettler, Matthieu; Broly, Hervé; Soos, Miroslav; Morbidelli, Massimo (Journal of biotechnology, 2018)
The pharmaceutical production of recombinant proteins, such as monoclonal antibodies, is rather complex and requires proper development work. Accordingly, it is essential to develop appropriate scale-down models, which can mimic the corresponding production scale. In this work, we investigated the impact of the bioreactor scale on intracellular micro-heterogeneities of a CHO cell line producing monoclonal antibodies in fed-batch mode, using a 10 mL micro-bioreactor (ambr™) scale-down model and the corresponding 300 L pilot-scale bioreactor. For each scale, we measured the time evolution of the proteome, which enabled us to compare the impact of the bioreactor scale on the intracellular processes. Nearly absolute accordance between the scales was verified by data mining methods, such as hierarchical clustering and in-detail analysis on a single protein base. The time response of principal enzymes related to N-glycosylation was discussed, emphasizing major dissimilarities between the glycan fractions adorning the heavy chain and the corresponding protein abundance. The enzyme expression displayed mainly a constant profile, whereas the resulting glycan pattern changed over time. It is concluded that the enzymatic activity is influenced by the changing environmental conditions present in the fed-batch processes leading to the observed time-dependent variation.
Keywords: CHO buňky; křečci praví; Proteomics; Antibodies, Monoclonal; Models, Biological; Cluster Analysis; Recombinant Proteins; zvířata; proliferace buněk; CHO Cells; proteomika; Cricetulus; rekombinantní proteiny; glykosylace; Cell Proliferation; biologické modely; shluková analýza; monoklonální protilátky; Bioreactors; Cricetinae; Animals; Glycosylation; bioreaktory